Conditions for formation of healthy lifestyle of students in physical education - E. M. Batenko; M. V. Bugay (Омский научный вестник: Серия "Общество. История. Современность")
This article discusses the problem of organizing physical education in a higher education institution in light of formation of healthy lifestyle of students. External factors influencing the person, methods of education in universities, according to the legislation of the Russian Federation, as well as proper self-organization in this area are analyzed